2020
DOI: 10.21203/rs.2.17176/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A cross-sectional study of the relationships between different components of sarcopenia and brachial ankle pulse wave velocity in community-dwelling elderly

Abstract: Background Declination of skeletal muscle mass or sarcopenia is associated with the arterial stiffness. However, but it is unclear whether muscle strength and physical performance; important contributors of sarcopenia are associated with the arterial stiffness. The aim of this study was to investigate the relationship between sarcopenia, the components of sarcopenia and arterial stiffness among elderly population. Methods Four hundred and fifty community dwelling elderly participants (266 male, and 184 female,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Tanaka et al previously reported that relative skeletal muscle mass index had a negative relation with baPWV; however, such association became marginal after adjusting for %trunk fat or visceral fat area in postmenopausal women with T2DM [31]. Recently, a community-based cross-sectional study aimed at investigating the relationship between baPWV and different components of sarcopenia found that increased baPWV was associated with lower appendicular skeletal muscle index and handgrip strength [32]. Another study including 366 healthy adults in UK has also found a clear increase in arterial stiffness, as evaluated by the cardio-ankle vascular index, associated with increased age and skeletal mass index (SMI) level [33], without accounting for confounding variables, for example, malnutrition, activity, metabolic disorders, and liver and kidney disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka et al previously reported that relative skeletal muscle mass index had a negative relation with baPWV; however, such association became marginal after adjusting for %trunk fat or visceral fat area in postmenopausal women with T2DM [31]. Recently, a community-based cross-sectional study aimed at investigating the relationship between baPWV and different components of sarcopenia found that increased baPWV was associated with lower appendicular skeletal muscle index and handgrip strength [32]. Another study including 366 healthy adults in UK has also found a clear increase in arterial stiffness, as evaluated by the cardio-ankle vascular index, associated with increased age and skeletal mass index (SMI) level [33], without accounting for confounding variables, for example, malnutrition, activity, metabolic disorders, and liver and kidney disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The normal range of baPWV was defined as <1400 cm/s, and elevated AS was defined as baPWV ≥1400 cm/s. 12,23,24…”
Section: Methodsmentioning
confidence: 99%
“…Sarcopenia is defined as decreased skeletal muscle mass and function, and is an important cause of frailty in the elderly [1][2][3][4][5] . It has been reported that around 50 million people worldwide have sarcopenia, which affects 13% of individuals aged 60-70 years 6,7 .…”
mentioning
confidence: 99%
“…Sarcopenia is associated with increased risks of falls and fractures in elderly individuals, which may further increase the mortality rates of elderly populations 9 . The consequences of sarcopenia also include increased physical disability, lower quality of life, higher mortality, and increased rates of cardiovascular disease (CVD) with a poor prognosis 2,6,7 .…”
mentioning
confidence: 99%
See 1 more Smart Citation